IMPLEMENTASI AKAD IJAROH UNTUK PENDIDIKAN STUDI ANALISIS KOPERASI PELABUHAN INDONESIA III - Romaji; Dewi Riza Lisvi Vahlevi (ICO EDUSHA, 2021)
Educating the nation is one of the goals of the state according to the mandate of the 1945 Constitution. However, until the age of 71 years of Indonesian independence, people's lives still do not have access to proper formal education. there are certain groups of children who are most vulnerable to the impact, most of whom come from poor families so they are unable to continue their education to the next level. According to data from the Central Statistics Agency, there was an average increase in the cost of education by 6% in the 2015 to 2017 range, especially at the tertiary level. Because the high cost of education in Indonesia causes children to drop out of school, some of those who are not lucky have to work for earn a living. What will happen if the future of the nation is cut off in the middle of getting an education or even if they never get an education at all?The Indonesian Port Cooperative III comes with various products, one of which is Ijarah multiservice. Multi-service ijarah is a form of service product in the Indonesian Port Cooperative III. This product is to finance various services. One of them is for the cost of education. Multi-service ijarah is a lease transaction with an ijarah contract for services in obtaining benefits for a service where the bank will receive compensation in the form of wages (ujrah) or rent. This contract is applied to Islamic banking. Keywords: Ijaroh contract for the world of education References Ascarya. 2011. Akad & Produk Bank Syariah. Cetakan Ketiga. Jakarta: Rajawali Pers. Ascarya. 2012. Akad & Produk Bank Syariah. Jakarta: PT Raja Grafindo Persada Mardani. 2012. Fiqh Ekonomi Syari’ah: Fiqh Muamalah. Jakarta: Kencana Lailatul, Nur. 2020. Implementasi akad ijarah multijasa sector pendidikan: studi kasus Bank CIMB Niaga Syariah. Jurnal Mardiyah. 2014. Pembiayaan ijarah multijasa sebagai alternative sumber pembiayaan pendidikan (kajian terhadap fatwa dewan syariah nasional No. 44/DSN-MUI/VIII/2004 tentang pembiayaah multijasa. Jurnal Mar’atus,َّA.َّ2014.َّPenerapan akad ijarah pada pembiayaan multijasa dalam prespektif hokum islam. Jurnal Miles, Mattew B dan Amichael Huberman. 2007. Analisis Data Kualitatif Buku Sumber tentang Metode-Metode Baru. Terjemahan Tjetjep Rohendi Rohisi. Jakarta: Universitas Indonesia Moleong, Lexy J. 2013. Edisi Revisi. Bandung : PT. Remaja Rosdakarya Muhammad. 2014. Manajemen Pembiayaan Koperasi Syari’ah. Jakarta: UPP AMP YKPN. Nasrul. 2019. Implementasi Akad Al-Ijarah Al-Maushufah Fi Al-dzimmah sebagai alternative pembiayaan di lembaga keuangan syariah di Indonesia. Jurnal Setia, R. 2020. Implementasi Akad Ijarah Pada Pembiayaan Pendidikan di KSSU Harum Dhaha Kediri. Jurnal Sugiyono. 2009. Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung : Alfabeta Umam, Khotibul.2016. Perbankan Syariah. Jakarta: PT Raja Grafindo Persada.